Cryptic Female Choice in Arthropods 2015
DOI: 10.1007/978-3-319-17894-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Female Choice in Crustaceans

Abstract: Cryptic female choice may be common among crustaceans , but few studies have thoroughly examined it in this diverse taxonomic group. Herein, we summarize current genetic evidence for multiple paternity and skewed offspring ratios in crustaceans, and document observations that could suggest cryptic female choice. Behaviors indicative of cryptic female choice have been reported from numerous crustacean taxa (e.g., crayfish , hermit crabs , isopods ), showcasing a diverse array of behavioral mechanisms such as fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 167 publications
0
12
0
Order By: Relevance
“…Moreover, there are species like the snow crab, where females are highly polyandrous, yet they exhibit mostly single paternity (Sainte-Marie et al 2008). For a more extensive list of examples of multiple paternity in crustaceans see Dennenmoser and Thiel (2015). What factors or life history attributes influence the existence and prevalence of multiple mating?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, there are species like the snow crab, where females are highly polyandrous, yet they exhibit mostly single paternity (Sainte-Marie et al 2008). For a more extensive list of examples of multiple paternity in crustaceans see Dennenmoser and Thiel (2015). What factors or life history attributes influence the existence and prevalence of multiple mating?…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns have been found in other crustaceans: O. placidus (Walker et al 2002), C. ensifera (Yue and Chang 2010), P. clarkii , M. magister (Jensen and Bentzen 2012), D. primitivus (Jossart et al 2014) and R. typus (Bailie et al 2014). The causes for this skew vary and likely include pre-copulatory factors such as mating order , female choice, where the female mates several times with a preferred male (Thiel and Correa 2004), or different sperm contribution (ejaculate size) (Rondeau and Sainte-Marie 2001; Probability of detecting multiple mating in A. pelagica combining the four loci with the highest individual probability (Acpe20, Acpe26, Acpe51 and Acpe57) at different sample sizes, assuming 2 sires with a skew contribution to the offspring (90 and 10 %, respectively) Sato et al 2005;Pugh et al 2015;Moyano et al2015) or post-copulatory sperm competition or selection, which could happen by sperm digestion or by sperm sorting and differential use (Haase and Baur 1995;Thiel and Hinojosa 2003;Yue and Chang 2010;Dennenmoser and Thiel 2015). Within the caridean group, it has been observed that females of the species R. typus manipulate spermatophores and spawning time, in order to discriminate undesired males and favor preferred males (Thiel and Hinojosa 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This cost is a result of spermatozoa being delivered together with accessory fluids (Dewsbury 1982). These fluids may be involved in many tasks, like maintaining spermatozoa, generating reluctance to mate with a subsequent male, (Chapman 2001;Arnqvist & Andrés 2006), or contributing to the formation of a genital plug (Kaufman et al 2008;Dennenmoser & Thiel 2015).…”
mentioning
confidence: 99%